Designing of Book Illustration Techniques Playing Blues On Guitar - Herda Cahya Mustika S1 (Saraswati)
emotion or soul anxiety. Blues music has a great influence on American popular music and Western[1]. Blues are popular / known in general often played using the guitar, the guitar blues there are several techniques used, the vibrato / vibra, sliding, hammer on pull off, rake picking and bending. In this design blues packaged in a book illustration is edutainment. Blues are often shown and connection between the cowboy lifestyle, which represent visual accent and to be applied in the design of book illustration this time is where the book is illustrated using a fictional character to suit the visual accents of the characters white blues guitarist who had renowned blues guitarist and an icon, like the one of which is the SRV (Stevie Ray Vaughan). At this time the design is slightly different blues presented by applying the Art Nouveau style design. Style illustrations used are a mix of illustration style articles, Vignette and illustration style short story / novel / romance.   Keywords: blues, cowboy (Stevie Ray Vaughan), art nouveau.   [1] Blues, id.wikipedia.org (22:52/14/02/13)